The Effect of the Realization of Public Service Agency Work Unit Expenditure on Education and Health and GDP on the Human Development Index (HDI) in Makassar City - Arruanlinggi, Heronimus; Baharuddin, Dahlia; Selong, Abbas (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This research was conducted with the following objectives: (1). To find out and analyze the influence of the Realization of Expenditure of the Public Service Agency of the Education Cluster on the Human Development Index (HDI) in Makassar City. (2). To find out and analyze the effect of the Realization of Expenditure of the Public Service Agency of the Health Cluster on the Human Development Index (HDI) in Makassar City. (3). To find out and analyze the influence of GDP on the Human Development Index (HDI) in Makassar City. This study uses Multiple Linear Regression analysis. The data used is secondary data for 11 years. Based on the results of the research conducted by the researcher, the researcher concluded that (1). The realization of the Education BLU Work Unit Expenditure has a negative positive effect on the Human Development Index (HDI), in Makassar City (2). The realization of the Expenditure of the BLU Health Work Unit has a positive and insignificant effect on the Human Development Index (HDI), in Makassar City. (3). GDP has a significant positive effect on the Human Development Index (HDI), in Makassar City.